Law as Performance: Sovereignty, Legal Indeterminacy, and the Chinese Private Security Industry - Pouliot, Alexandrya (AUC Knowledge Fountain, 2025)
This thesis examines how the legal indeterminacy of international law facilitates state evasion of accountability through the use of private military and security companies (PMSCs) as proxies in extraterritorial operations. Focusing on China’s deployment of PSCs to safeguard Belt and Road Initiative (BRI) projects, it argues that ambiguities within the doctrines of attribution and responsibility under the Articles on the Responsibility of States for Internationally Wrongful Acts (ARSIWA) create a permissive legal environment that enables states to outsource coercive functions without incurring formal liability. Drawing upon Hobbesian Realist theory, Carl Schmitt’s concept of the sovereign exception, and insights from Critical Legal Theory (CLT), the study demonstrates that legal ambiguity is not a flaw but a structural feature of the international legal order: one that perpetuates and conceals power asymmetries amongst states. China is presented as a ‘cautious Schmittian sovereign,’ strategically invoking or suspending legal norms to advance geopolitical aims while maintaining formal insulation from accountability under International Humanitarian Law (IHL) and state responsibility frameworks. By combining doctrinal analysis with critical theory, the thesis situates the Chinese case within a broader pattern in which international law functions less as a constraint and more as an instrument for managing visibility, shaping legality, and preserving sovereign discretion in the contemporary international order.